2004
DOI: 10.1007/s10120-004-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic characteristics of gastric cancer in the elderly: a retrospective study of 994 surgical patients

Abstract: Background. The clinicopathologic features of gastric carcinoma in elderly people have been reported previously. The present study examined the patterns and distribution of gastric carcinomas in the elderly, especially in patients aged 85 and older. Methods. A retrospective study of 994 consecutive Japanese patients aged 65 years or older was performed. In this group, a total of 1147 lesions were analyzed. Pathological findings in the very old group (older than 85 years; n ‫؍‬ 126) were compared with those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 20 publications
7
98
2
Order By: Relevance
“…The proportion of proximal colonic cancer in women was approximately 10% higher than those in men, and increased with advancing age. 29 Molecular evidence showed colorectal cancer with microsatellite instability was most frequent among younger male and older female patients. 12,30 The frequency of hMLH1 methylation with lack of its expression was significantly correlated with females and aging.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of proximal colonic cancer in women was approximately 10% higher than those in men, and increased with advancing age. 29 Molecular evidence showed colorectal cancer with microsatellite instability was most frequent among younger male and older female patients. 12,30 The frequency of hMLH1 methylation with lack of its expression was significantly correlated with females and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumor intragastric location in elderly gastric cancer patients, the vast majority of studies have documented predominance of lower or distal third gastric location, independently of pathological stage [14][15][16][17]. The incidence of lower or distal third gastric cancer in the elderly varies between 42-63%, which is significantly higher than that observed in younger patients (aged 65-74) (31% -44%) [2,14,[16][17].…”
Section: Tumor Intragastic Locationmentioning
confidence: 99%
“…The incidence of lower or distal third gastric cancer in the elderly varies between 42-63%, which is significantly higher than that observed in younger patients (aged 65-74) (31% -44%) [2,14,[16][17].…”
Section: Tumor Intragastic Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, controversy remains about the influence of chronologic age on the nodal status in gastric carcinoma. Most previous reports have negated a significant difference in the rates of LN metastasis between younger and elderly patients [37][38][39][40], whereas in cases of early gastric cancer several authors have reported a higher prevalence of LN involvement for elderly patients [41,42].…”
Section: Survival Analysismentioning
confidence: 99%